Fabrication Of Phantom For Quality Assurance Assessment In Cardiac Spect Imaging - Sayah, Mohannad Adel Mustafa (2018)
Single-photon emission computed tomography (SPECT) is commonly used in nuclear imaging to detect myocardial infarction (MI) within a myocardial wall (MW). SPECT can identify areas of infarction in MW. In this work, a MI phantom was fabricated and designed to simulate the MW of the left ventricle (MWLV) in the end-diastole and end-systole stages. This work aimed to assess the MI phantom in both stages as a part of quality assurance assessment in cardiac SPECT imaging. In the end-diastole stage, when the defects were fixed at the anterior and inferior walls, the minimum detectable thickness was 2 mm regardless of the position of the phantom on the imaging table.